9-day high-grade spiking postoperative fever in a child with acute appendicitis: facing clinical systemic disorders in surgery setting. Issue 1 (2021) - Ugolini, Sara; Rosati, Giovanni Vitali; Coletta, Riccardo; Simonini, Gabriele; Morabito, Antonino
No abstract available